Experimental study on dust explosion vented through a bent duct. Issue 1 (16th June 2020) - Pang, Lei; Zhang, Zhiwen; Cui, Shiqi; Yuan, Chunmiao; Zhu, Xinrui; Yin, Jiaxin; Sun, Siheng
Abstract: In this study, a self‐designed small cylindrical vessel was used to perform a dust explosion venting experiment through a bent duct. Based on this experiment, the influence of the bend distance and the static activation overpressure of the venting film on the explosion overpressure and the flame propagation was investigated. The results showed that both the maximum venting overpressure and pressure rise rate within the vessel increased with the decrease in the bend distance and increase in the static activation overpressure. In contrast, the duration of the combustion within the vessel exhibited the opposite trend. A typical "three‐peak" overpressure structure formed by the film rupture shock wave, secondary explosion in the duct, and continuous combustion within the vessel was observed in the duct. The third peak overpressure was dominant throughout the process. The intensity of the secondary explosion in the duct was positively correlated with the bend distance and static activation overpressure. Shorter bend distances led to greater peak‐overpressure drops after passing the bend. However, the attenuation of the secondary explosion intensity along the duct with static activation overpressure is not obvious.